Iron(II)-Catalyzed Denitration Reaction: Synthesis of 3-Methyl-2-arylimidazo[1,2-a]pyridine Derivatives from Aminopyridines and 2-Methylnitroolefins - Yan, Hao; Yang, Sizhuo; Gao, Xiai; Zhou, Kang; Ma, Chao; Yan, Rulong; Huang, Guosheng (Synlett, 2012)
A variety of ways to synthesize imidazo[1,2-a]pyridines have been reported and many approaches are devoted to the functionalization of imidazo[1,2-a]pyridines. However, the use of a denitration reaction in the synthesis of imidazo[1,2-a]pyridines has not been reported. We report here the iron-catalyzed synthesis of 3-methyl-2-arylimidazo [1,2-a] pyridine derivatives from aminopyridines and 2-methyl-nitroolefins. The procedure, using FeCl2 as catalyst, is simple and inexpensive. Various functional groups are tolerated and provide the products in good yields.
Keywords: iron catalysis; denitration; heterocycles; cyclization; imidazo[1,2-a]pyridines